Behavioral games for triggering adoption of good agricultural practices: insights from women’s empowerment project in Telangana, India - Waris, Amtul (Indian Council of Agricultural Research, 2023)
In a creative endeavor for gender-transformative change in agri-food systems, a study was designed to use a behavioral game to trigger the adoption of good agricultural practices (GAPs) in a women’s empowerment project in Telangana, India. Based on insights from behavioral economics and game design, the traditional snakes and ladders game was adapted to disseminate GAPs among women farmers. The specific GAPs to be promoted were identified to be included in the behavior-change game. In this innovative approach, ladders symbolize GAPs, while snakes depict less desirable practices. Leveraging the versatility of Python’s open-source software, this game was crafted with ingenuity. Upon launching the game, the initial screen prompts players to input the number of participating farmers. Subsequently, virtual dice and coins are generated for each farmer. By initiating the game with the ‘play’ button, the virtual dice sets the game in motion, propelling tokens across the gameboard’s blocks. Positive reinforcement was through the in-game reward of climbing the ladder with the adoption of GAPs. The in-game progress to real-world outcomes was connected through demonstrations of selected GAPs on fields’ of women farmers. The alternate wetting and drying (AWD) method of rice crop establishment was demonstrated to show them how it translates in reality to improved crop yield (20.32%) and reduced water usage (14.49%) over the conventional flooded transplanting method. By incorporating game elements into the project, we planned to tap into psychological and behavioral drivers that encourage participants to adopt and sustain positive practices.